Treatment of cholestatic fibrosis by altering gene expression of Cthrc1: Implications for autoimmune and non-autoimmune liver disease. (September 2015) - Bian, Zhaolian; Miao, Qi; Zhong, Wei; Zhang, Haiyan; Wang, Qixia; Peng, Yanshen; Chen, Xiaoyu; Guo, Canjie; Shen, Li; Yang, Fan; Xu, Jie; Qiu, Dekai; et al.
Abstract: Collagen triple helix repeat containing-1 (Cthrc1) is a documented specific inhibitor of TGF-β signaling. Based on this observation, we developed the hypothesis that knocking in/knocking out the Cthrc1 gene in murine models of cholestasis would alter the natural history of cholestatic fibrosis. To study this thesis, we studied two murine models of fibrosis, first, common bile duct ligation (CBDL) and second, feeding of 3, 5-diethoxy-carbonyl-1, 4-dihydrocollidine (DDC). In both models, we administered well-defined adenoviral vectors that expressed either Cthrc1 or, alternatively, a short hairpin RNA (shRNA)-targeting Cthrc1 either before or after establishment of fibrosis. Importantly, when Cthrc1 gene expression was enhanced, we noted a significant improvement of hepatic fibrosis, both microscopically and by analysis of fibrotic gene expression. In contrast, when Cthrc1 gene expression was deleted, there was a significant exacerbation of fibrosis. To identify the mechanism of action of these significant effects produced by knocking in/knocking out Cthrc gene expression, we thence studied the interaction of Cthrc1 gene expression using hepatic stellate cells (HSCs) and human LX-2 cells. Importantly, we demonstrate that Cthrc1 is induced by TGF-β1 via phospho-Smad3 binding to the promoter with subsequent transcription activation. In addition, we demonstrate that Cthrc1 inhibits TGF-β signaling by accelerating degradation of phospho-Smad3 through a proteosomal pathway. Importantly, the anti-fibrotic effects can be recapitulated with a truncated fragment of Cthrc1. In conclusion, our findings uncover a critical negative feedback regulatory loop in which TGF-β1 induces Cthrc1, which can attenuate fibrosis by accelerating degradation of phospho-Smad3. Highlights: A major unmet need in autoimmunity and cholestatic liver disease is the prevention and treatment of fibrosis. Knocking in/knockout out the Cthrc1 gene significantly modulates cholestatic fibrosis in two murine models. The mechanism of Cthrc1 gene expression and its effect on fibrosis is by TGF-β1 via phospho-Smad3 binding. Cthrc1 inhibits TGF-β signaling through a proteosomal pathway. Use of truncated fragments of Cthrc1 may serve as a model to further understand fibrosis, but also as a therapeutic tool.